Cloze Procedure Technique on Students' Reading Comprehension of Descriptive Text - Elmiwati, Elmiwati; Mayasari, Eka; Putri, Desy Hadinda (Journal of Educational Review and Cultural Studies, 2023)
This research investigated the effectiveness of the cloze procedure technique on students' reading comprehension of descriptive texts and to find out students’ responses toward the cloze procedure technique proposed by Taylor Wilson. This research used experimental research and used quantitative data. The instrument was a reading test (pre-test, post-test) and a questionnaire with 15 questions. This study's population was all class X students, with a sample of 54 students. This research lasted for one month. In this study, it can be seen from the pre-test and post-test results that have been calculated using the Independent Sample T-test through the SPSS program that the significance was 0.001, which means that the cloze procedure technique is effective. In the questionnaire results, the answers (yes) were chosen from as many as 293 and (no) as many as 112, which meant that most students at SMA Negeri 1 Lingga Utara responded positively about the cloze procedure technique.